Making the Smallholder Farmers in Southeast Asia Climate Smart - The CCAFS R4D Thrust - Sebastian, Leocadio S.; Bernardo, Eisen Bernard (National Agriculture and Food Research Organization, 2019)
On September 27-28, 2018, the National Agriculture and Food Research Organization (NARO), FFTC and the Monsoon Asia A gro-Environmental Res earch Cons ortium (MARCO) held a symposium on “Climate Smart Agriculture for Small-scale Farmers in the Asian and Pacific Region” at the Tsukuba International Conference Center in Tsukuba, Japan. The said symposium aims to promote extensive research and development on the environment especially where it concerns sustainable agriculture. Fifteen speakers from eight countries (China, Japan, Indonesia, Taiwan, Philippines, France, Korea and Thailand) delivered various presentations divided into four sessions: 1) mitigation options for greenhouse gas emission from agricultural lands in the Asian and Pacific region; 2) mechanisms and impacts of global environmental change in crop production; 3) adaptation options to reduce vulnerability of agricultural systems to the risks related to climate change; and 4) decision support systems for improving the livelihood of farmers. After the workshop, FFTC and NARO decided to publish a collection of 22 selected papers presented during both the FFTC-NARO and MARCO symposium and the NARO International Peer Review Meeting. The book has three major sections: 1) mitigation options for greenhouse gas emissions from agricultural lands in the Asian Pacific region; 2) mechanisms and impacts of global environmental change on crop production in the Asian and Pacific region; and 3) adaptation options to reduce vulnerability of agricultural systems to the risks related to climate change in the Asian Pacific region. A chapter on making the smallholder farmers in Southeast Asia climate smart, written by Leocadio S. Sebastian and Eisen Bernard V. Bernardo of CCAFS SEA, is included in the book.